838Premature Cardiac Conduction Disease in families, potential role for Implantable Loop Recorder in screening? A Case Series. (18th June 2020) - Sharif, Z; Murphy, L M; Al-Harbi, K A H; Brennan, C B; Connaughton, H C; Green, A G; Ward, D W
Abstract: OnBehalf: Cardiac Risk in the Young (CRY) Ireland Background:   Cardiac conduction disease (CCD) is a potentially fatal entity. The spectrum ranges from benign clinical course to potentially precipitating sudden cardiac death. Permanent pacemaker (PPM) may benefit affected individuals but the genetic basis of CCD may be underestimated. No prior study has investigated the utility of screening relatives of victims of Sudden Arrhythmic Death Syndrome (SADS) with implantable loop recorders (ILR).  Methods:  We describe 7 families referred to our inherited cardiac conditions service with a family history of SADS, in whom we identified premature CCD. ILR was utilized in screening the majority of families.  Results:  Of 63 individuals screened, 31 (49%) had ILR insertion with 7 (11%) requiring PPM implant. 2/31 had normal baseline tests, and were identified post ILR implant. Other CCD not yet meeting clinical significance was detected in 10/31 (32%) individuals. These findings (documented 11 to 330 days post implant) included pauses of 3-5.8 seconds (n = 7), nocturnal bradycardia < 34 bpm (n = 2) and non-sustained polymorphic ventricular tachycardia. Of families undergoing mutation analysis, conventional genetic panels have been negative to date. Conclusions:  Inherited premature CCD with variable penetrance may be an under-recognized cause of SADS.  To date 12/31 (39%) of individuals with ILR have findings suggesting inherited CCD. As inheritance pattern suggests autosomal dominant transmission, longer follow up may identify more affected individuals. Clinicians involved in SADS family evaluations should consider adding ILR implantation to routine assessment to improve diagnostic yield. We suggest a larger prospective study of consecutive families whose initial investigations following a SADS death have not identified a cause.